2019
DOI: 10.1101/548156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adaptive efficient coding of correlated acoustic properties

Abstract: word)Natural sounds such as vocalizations often have co-varying acoustic attributes where one acoustic feature can be predicted from another, resulting in redundancy in neural coding. It has been proposed that sensory systems are able to detect such covariation and adapt to reduce redundancy, leading to more efficient neural coding. Results of recent psychoacoustic studies suggest that, following passive exposure to sounds in which temporal and spectral attributes covaried in a correlated fashion, the auditory… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 47 publications
0
7
1
Order By: Relevance
“…While the neural locus or loci responsible for these human perceptual findings remains an open question, multiple neurophysiological studies with animal models are instructive. Most recently, findings by Stilp and colleagues have been replicated in neural response in primary auditory cortex of ferrets upon presentation of sounds that covaried in amplitude modulation and peak frequency of the spectral envelope (Lu, Liu, Dutta, Fritz, & Shamma, 2019). Following exposure to stimuli capturing these correlated attributes, signal-to-noise ratio (SNR) of spike-rate coding decreased orthogonal to the correlation, while remaining intact along the correlation; and, mutual information of spike coding increased only along the correlated dimension.…”
Section: Learning Correlations Among Stimulus Attributesmentioning
confidence: 89%
“…While the neural locus or loci responsible for these human perceptual findings remains an open question, multiple neurophysiological studies with animal models are instructive. Most recently, findings by Stilp and colleagues have been replicated in neural response in primary auditory cortex of ferrets upon presentation of sounds that covaried in amplitude modulation and peak frequency of the spectral envelope (Lu, Liu, Dutta, Fritz, & Shamma, 2019). Following exposure to stimuli capturing these correlated attributes, signal-to-noise ratio (SNR) of spike-rate coding decreased orthogonal to the correlation, while remaining intact along the correlation; and, mutual information of spike coding increased only along the correlated dimension.…”
Section: Learning Correlations Among Stimulus Attributesmentioning
confidence: 89%
“…If underlying representations change as a consequence of short-term passive exposure to regularities as suggested in prior research (Lu et al, 2019;Stilp & Kluender, 2012;Stilp et al, 2010) one might predict that this exposure also would impact how participants use acoustic information learn novel categories. The basis of this expectation stems from a substantial literature demonstrating that the input dimensions across which category exemplars are defined and the sampling of exemplars from an input space are crucial in predicting how category learning proceeds (Ashby & Maddox, 2011;Folstein, Gauthier, & Palmeri, 2010;Gureckis & Goldstone, 2008;Maye et al, 2002;Smith, Jayaraman, Clerkin, & Yu, 2018;Werker, Yeung, & Yoshida, 2012).…”
Section: Inefficient Coding: Limits Of the Effects Of Short-term Exposure To Statistical Regularities On Representations And Behaviormentioning
confidence: 92%
“…These prior investigations (Stilp & Kluender, 2012;Stilp et al, 2010) have focused on one kind of relationship (positive or negative correlation) in one acoustic environment (attack-decay and spectral shape) and examined behavior using discrimination measures. A recent study found that neurons in ferret auditory cortex reflect rapid efficient coding of correlations of similar acoustic attributes (peak frequency of the spectral envelope and amplitude modulation; Lu et al, 2019). These prior studies highlight that sensory systems are able to rapidly adapt to novel regularities reflecting correlations between acoustic attributes changing both discrimination behavior and neural tuning in auditory cortex.…”
Section: Inefficient Coding: Limits Of the Effects Of Short-term Exposure To Statistical Regularities On Representations And Behaviormentioning
confidence: 97%
See 2 more Smart Citations